2007
DOI: 10.1111/j.1461-0248.2007.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Time, transients and elasticity

Abstract: How does life history affects the short-term elasticities of population growth rate? We decompose short-term elasticity as a sum of (i) the effect of the perturbation in rates on the unperturbed population structure and (ii) the effect of the original vital rates on the difference in structure between the original and the perturbed population. We provide exact analytical formulas for these components. In a population at its stable stage distribution (SSD), short-term elasticity is determined mainly by the SSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 16 publications
1
71
0
Order By: Relevance
“…I calculated the average transient growth rate r(t1,t2) by projecting the population over 10 years using eqn ():rfalse(t1,t2false)=1t2t1logN(t2)N(t1),with initial population vector n (0) equal to the average observed population structure over the 4‐year study. Transient dynamics are sensitive to initial population structure (Haridas & Tuljapurkar ; Stott, Townley & Hodgson ; Stott, Hodgson & Townley ). One could use different n (0) (dominated by adults, or by seedlings, or stable stage distribution) to test how initial conditions may change transient dynamics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I calculated the average transient growth rate r(t1,t2) by projecting the population over 10 years using eqn ():rfalse(t1,t2false)=1t2t1logN(t2)N(t1),with initial population vector n (0) equal to the average observed population structure over the 4‐year study. Transient dynamics are sensitive to initial population structure (Haridas & Tuljapurkar ; Stott, Townley & Hodgson ; Stott, Hodgson & Townley ). One could use different n (0) (dominated by adults, or by seedlings, or stable stage distribution) to test how initial conditions may change transient dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…; Miller & Tenhumberg ; Stott, Hodgson & Townley ; Tremblay, Raventos & Ackerman ). Transient elasticities can be temporally dynamic (Haridas & Tuljapurkar ; Yearsley ). For example, Maron, Horvitz & Williams () showed that the relative importance of fertility for transient growth of the invasive Cynoglossum officinale varies over time and between native and invasive ranges, oscillating in one environment and phasing each other in another.…”
Section: Introductionmentioning
confidence: 99%
“…In some scenarios, earlier life stages disproportionally contributed to the population growth rate of long‐lived species over the short‐term (e.g. 10 years), relative to later life stages (Haridas & Tuljapurkar ; McMahon & Metcalf ; Ezard et al . ; Haridas & Gerber ; Gaoue ).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the relative importance of life stages on the short‐term population growth rate, we conducted stochastic transient elasticity analyses with respect to small changes in matrix elements to unperturbed stage structure, e 1, i , j (Haridas & Tuljapurkar ; Haridas & Gerber ). The e 1, i , j distribution for each scenario ( A , B , C , and D ) was iteratively calculated by simulation, using 1000 iterations.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term behavior, however, can be different from its long-term behavior because, unlike asymptotic rates, transient growth rates can be strongly influenced by the population current age or size distribution (Caswell and Werner 1978;Caswell 1989;Burgman et al 1993;Caswell 2007). Haridas and Tuljapurkar (2007) showed that it is possible to have only properties of the unperturbed vital rates and stage structure of a population to predict short-term responses to perturbations, and should therefore be useful in several management contexts.…”
Section: Introductionmentioning
confidence: 99%